2002
DOI: 10.1073/pnas.152320899
|View full text |Cite
|
Sign up to set email alerts
|

SCORE: A computational approach to the identification of cis-regulatory modules and target genes in whole-genome sequence data

Abstract: A large fraction of the information content of metazoan genomes resides in the transcriptional and posttranscriptional cis-regulatory elements that collectively provide the blueprint for using the proteincoding capacity of the DNA, thus guiding the development and physiology of the entire organism. As successive whole-genome sequencing projects--including those of mice and humans-are completed, we have full access to the regulatory genome of yet another species. But our ability to decipher the cis-regulatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 35 publications
0
110
0
Order By: Relevance
“…Statistically significant clustering of TF binding sites has proven to be a valuable criterion for the identification of functional CRMs (12,25). We applied a two-motif version of the SCORE computational technique (12) to recognize several NP-specific enhancers in the fly genome. In the case of three genes (phyl, sens, and nvy), the newly identified NP module is distinct from another one previously reported, establishing the existence of a dual-enhancer configuration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistically significant clustering of TF binding sites has proven to be a valuable criterion for the identification of functional CRMs (12,25). We applied a two-motif version of the SCORE computational technique (12) to recognize several NP-specific enhancers in the fly genome. In the case of three genes (phyl, sens, and nvy), the newly identified NP module is distinct from another one previously reported, establishing the existence of a dual-enhancer configuration.…”
Section: Discussionmentioning
confidence: 99%
“…S1) suggested that additional SOP-specific [or, more generally, neural precursor (NP)-specific] enhancer modules might be identifiable on this basis. Accordingly, we used the SCORE computational method (12) to survey the Drosophila genome for statistically significant coclustering of P and R motifs. We detected such clusters in association with several known NP-expressed genes, including phyllopod (phyl), senseless (sens), and nervy (nvy) (Fig.…”
Section: Computational Identification Of Motif Clusters Representing mentioning
confidence: 99%
See 1 more Smart Citation
“…One clue is found in the promoter regions of a number of well characterized Notch-responsive genes (19), such as the hairy/enhancerof-split genes in Drosophila and a number of their mammalian homologues, which contain dual ''sequence-paired'' binding sites (SPSs) (20,21). SPSs consist of two CSL-binding sites oriented head-to-head that typically are separated by 16 or 17 nt, depending on the species examined [supporting information (SI) Fig.…”
mentioning
confidence: 99%
“…Homotypic clusters have been widely studied in Drosophila [157][158][159], but are yet relatively unexplored in mammalian genomes. A large fraction of methods use a set of elements believed to be functional in a particular process or cell type and train a model based on the frequencies and relative distributions of motifs within them.…”
Section: Human Tsssmentioning
confidence: 99%